Avaliação de sistema estabilizante para cobertura de cabos aéreos em XLPE - Feresin, Fábio (2005)
Overhead energy lines with covered conductors are increasingly used in the 15 kV distribution systems in Brazil. The advantages are, among others, reduced distances between phases, no disruptions due to conductor clashes, maintained withstand strength when fallen trees touch the line and simple mounting. However, the service reliability of overhead lines with covered conductors in our exposed climate is not quite clarified; normally the specification requirement gives a good performance. When the compounds are formulated to have sunlight and thermal resistance at the same time, because the cables normally work at 90°C conductor temperature, the relationship between both stabilizers becomes very important. The work developed and based on 2² factorial with centroid design taking in account two stabilizers as influent factor to be investigated as well their interactions by measuring the mechanical properties and oxidation temperature. One compound group wereas exposed during eighth thousand hour in weatherometer and the other group, at temperatures of 140°C, 150°C e and 160°C, in the oven. A high performance of the hindered phenol antioxidant was observed during thermo-oxidative degradation and no effectiveness was observed during the photo-oxidative degradation. In the order hand, a great performance of polymeric HALS was observed during photo-oxidation ands a quite good performance was observed as thermal-oxidative stabiliser. An antagonist effect was observed whith this two types of stabilizers used, during photo or thermaloxidative degradations, related with aditives concentrations or rates.